International Monetary Fund Administrative Tribunal Reports, Volume IV, 2005. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
Volume IV of IMF Administrative Tribunal Reports contains the Judgments and Orders of the IMF Administrative Tribunal rendered during the year 2005. An analysis of the Tribunal's jurisprudence for the period is provided in an introductory chapter 'Developments in the Jurisprudence of the IMF Administrative Tribunal: 2005.' A detailed topical Index of the Judgments and Orders is included near the end of the volume. Finally, the reader will find republished as an Appendix to this volume the Tribunal's Statute, Rules of Procedure, and the Report of the International Monetary Fund's Executive Board on the establishment of the Administrative Tribunal. The Tribunal initially addressed the Applicant's principal claim, that the abolition of his position represented an abuse of managerial discretion. Referring to the governing provisions of the IMF's internal law, the Tribunal noted that the essential requirements for a lawful abolition of position are that the position has been abolished or redesigned to meet institutional needs and the incumbent is no longer qualified to fulfill its requirements.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet